CyberUnion: Empowering Labour through Computer Technology - Fiorito, Jack (Relations industrielles / Industrial Relations, 2001)
CyberUnion: Empowering Labor through Computer Technology, by Arthur B. Shostak, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; information technology